Art in action : toward a Christian aesthetic - Wolterstorff, Nicholas (Michigan : Grand Rapids : William B. Eerdmans Publishing Company, 1980)
Taking vigorous issue with the pervasive Western notion that the arts exist essentially for the purpose of aesthetic contemplation, Nicholas Wolterstorff proposes instead what he sees as an authentically Christian perspective: that art has a legitimate, even necessary, place in everyday life. While granting that galleries, theaters and concert halls serve a valid purpose, Wolterstorff argues that art should also be appreciated in action -- in private homes, in hotel lobbies, in factories and grocery stores, on main street. His conviction that art should be multifunction is basic to the author's views on art in the city (he regards most American cities as dehumanizing wastelands of aesthetic squalor, dominated by the demands of the automobile), and leads him to a helpful discussion of its role in worship and the church. Developing an aesthetic that is basically grounded, yet always sensitive to the human need for beauty, Wolterstorff make a brilliant contribution to understanding how art can serve to broaden and enrich our lives
Artistically Man Acts -- Art in Action -- The Universality of Art -- The Purpose of Art -- The Arts -- The Essential Purpose of Art -- Intended Public Use of Art -- Our Blindness -- The Structure of Art in Action -- Works of Art -- Our Institution of High Art -- Our Institution of High Art -- Art for Contemplation -- Separation of Art from Life -- Immensity of Repertoire -- The Critic in Our Institution of High Art -- The Purpose for the Uses -- Contemplation for Its Own Sake -- Disinterested Contemplation and the Fine Arts -- The Aesthetic -- Inscape -- Stylistic Diversity -- Mysticism and the Religion of the Aesthetic -- Artistic Creation -- The Interiorizing of the Artist Community -- Anti-Art and De-aestheticization -- Art in Christian Perspective -- The Artist as Responsible Servant -- Toward a Christian Aesthetic -- Man an Earthling -- Man's Vocation -- Man's End -- Redemption -- The Protestant View -- The World Behind the Work -- The Given With Which the Artist Works -- The Artist and His Medium--Mastering -- The Artist and Fittingness -- The Nature of Fittingness -- Expressiveness -- Worker in Fittingness -- The Action of World-Projection -- In and Out of Worlds -- The Ontology of Worlds -- The Action of Projection -- Point of View -- The Benefits of World-Projection -- Marcuse on the Benefits of World-Projection -- Norms in Art: Artistic and Aesthetic Responsibility -- Artistic Excellence -- Aesthetic Excellence -- Aspects Irrelevant to Aesthetic Excellence -- Beauty -- Types of Aesthetic Merit
Includes bibliographical references (pages 239-240)
Keywords: Christianity and the arts